2017
DOI: 10.1155/2017/7674240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shizhifang on NLRP3 Inflammasome Activation and Renal Tubular Injury in Hyperuricemic Rats

Abstract: Objective Uric acid (UA) activates the NLRP3-ASC-caspase-1 axis and triggers cascade inflammatory that leads to hyperuricemic nephropathy and hyperuricemia-induced renal tubular injury. The original study aims to verify the positive effects of the traditional Chinese medicinal formula Shizhifang (SZF) on ameliorating the hyperuricemia, tubular injury, and inflammasome infiltration in the kidneys of hyperuricemic lab rats. Method Twenty-eight male Sprague-Dawley rats were divided into four groups: control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The above studies have described that traditional Chinese medicine can reduce uric acid levels in the body by inhibiting the inflammatory state of hyperuricemia or regulating the expression of uric acid transporter or regulating XOD activity, or through a combination. The anti-inflammation effect of SZF has been reported in our previous study [ 45 ]. This article explores its effect on uric acid metabolism ulteriorly.…”
Section: Discussionsupporting
confidence: 58%
“…The above studies have described that traditional Chinese medicine can reduce uric acid levels in the body by inhibiting the inflammatory state of hyperuricemia or regulating the expression of uric acid transporter or regulating XOD activity, or through a combination. The anti-inflammation effect of SZF has been reported in our previous study [ 45 ]. This article explores its effect on uric acid metabolism ulteriorly.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, the HN mice showed a significant decrease in renal function with the increased Scr, BUN, and kidney injury biomarkers (NGAL, cystatin C Kim-1, and IL-18). Moreover, we discovered that NLRP3 inflammasome activation in HN injury, and upregulation of Bax, cleaved caspase-3 and caspase-9, while downregulation of Bcl-2 were observed in the HN kidney tissues, which was consistent with previous studies (Wu et al, 2017;Wang et al, 2018;Tan et al, 2019;Zhang et al, 2019). Therefore, using a properly scientific approach to test whether a therapeutic drug could inhibit NLRP3 inflammasome activation and apoptosis in HN provided evidence-based guidance for clinical practice.…”
Section: Discussionsupporting
confidence: 88%
“…As mentioned above, the release of pro-inflammatory cytokines is the key of kidney inflammation, and NLRP3 inflammatory pathway plays a crucial role in regulating inflammation ( Wu et al, 2017 ). The NLRP3 inflammasome is an intracellular multiprotein complex composed of a receptor NLRP3 (NACHT, LRR, and PYD domain-containing protein 3, cytosolic sensor protein), an adaptor ASC (an apoptosis-associated speck-like protein containing a caspase recruitment domain), and an effector caspase-1 (cysteinyl aspartate specific proteinase-1).…”
Section: Discussionmentioning
confidence: 99%